A Novel Case of Proliferative Diabetic Retinopathy In A Patient With Cone Rod Dystrophy - Yan, Keying; Eleff, Tybee; Zhou, Zimei (Canadian Journal of Optometry, 2023)
Diabetic retinopathy and retinal dystrophies rarely present concurrently due to the protective effect of retinal dystrophies against diabetic retinopathy, and there is little written in the literature documenting the co-existence of diabetic retinopathy and retinal dystrophies. This report describes a rare case of proliferative diabetic retinopathy (PDR) in a patient with cone rod dystrophy (CRD). This co-existence is not only unique in its presentation but also highlights the important role of ancillary testing including fundus autofluorescence, fluorescein angiography, optical coherence tomography, and full field electroretinography. In addition to these, genetic testing also aids in the determination of the diagnosis. The pathophysiology of the concurrent development of these conditions is discussed and underlines the need for further investigation into the pathophysiology of diabetic retinopathy, particularly in patients with retinal dystrophies.